Evaluating the Role of Computed Tomography Angiography in Assessing Return-to-Fly in Pilots with Coronary Artery Disease: An Evidence Based Virtual Case Report - Rachmy Hamdiyati; Anugrah Dwi Riski; Monica Djaja Saputera; Ferdi Afian (Hanggong uju uihakoeji, 2025)
In the aviation industry, coronary artery disease (CAD) is a serious concern for aviation authorities due to its potential impact on flight safety. One of the aeromedical concerns for pilots with CAD is the possibility of sudden cardiac arrest. Coronary computed tomography angiography (CCTA) is one of the recommended screening methods for cardiovascular diseases among air crew. This evidence-based case report aims to examine the use of CCTA as a prognostic tool for determining return-to-fly status in pilots with CAD. A comprehensive search of relevant articles was conducted in PubMed, ProQuest, Cochrane, and Ingenta library databases, leading to the identification of six articles that met the inclusion criteria. After a thorough critical appraisal, all of the articles were found to be valid, important, and applicable, with a level of evidence ranging from II–IV. These studies demonstrate the potential of CCTA as a valuable tool to assist in determining return-to-fly status in pilots with CAD. However, it is essential to conduct studies with larger sample sizes and higher quality standards to ascertain the test’s capacity to evaluate and manage CAD in pilots. This will ensure both individual and operational safety in the aviation industry.